(The Effect Of Adding Pectin On The Quality Of Tamarillo Marmalade - Najmi, Annisa; Holinesti, Rahmi; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Marmalade is a jam-like product with a thick texture and fruit pieces inside. It is made from fruit juice, fruit pieces, sugar, citric acid, and a gelling agent. Marmalade can serve as an alternative product for processing perishable ingredients like Tamarillo. Due to the limited variety of processed Tamarillo products, it is not a popular choice for consumption. However, when transformed into marmalade, Tamarillo has low pectin content, requiring the addition of pectin for optimal marmalade production. The aim of this research is to investigate the impact of adding pectin on the quality of Tamarillo marmalade. The expected benefits include optimizing the utilization of Tamarillo and enhancing its attractiveness and economic value. This study adopts a pure experimental design, specifically a true experiment, directly exploring the influence of pectin addition on Tamarillo marmalade quality. The research is conducted at the Workshop for Culinary Arts, Department of Family Welfare Sciences, Faculty of Tourism and Hospitality, Universitas Negeri Padang. Evaluation involves Organoleptic Testing by expert panels using a questionnaire as the research instrument. Data analysis employs Analysis of Variance (ANOVA) with four treatments and three replications. The observed marmalade qualities include color, aroma, texture, and taste. The results indicate that adding pectin at percentages of 0%, 1%, 1.5%, and 2% does not significantly affect the color, aroma, and taste of Tamarillo marmalade. However, the addition of pectin at these percentages significantly influences the thick and easily spreadable texture of Tamarillo marmalade.